Characterisation of allergen-specific responses of IL-10-producing regulatory B cells (Br1) in Cow Milk Allergy - Noh, Joonyong; Lee, Jae Ho; Noh, Geunwoong; Bang, So Young; Kim, Hyuk Soon; Choi, Wahn Soo; Cho, Sunheui; Lee, Sang Sun (Cellular immunology, 2010)
CD19+CD5+ regulatory B cells regulate immune responses by producing IL-10. IL-10-producing regulatory B cell (Br1) responses by allergen stimulation were investigated in human food allergy. Six milk allergy patients and eight milk-tolerant subjects were selected according to DBPCFC. PBMCs were stimulated by casein in vitro and stained for intracellular IL-10 and apoptosis. In response to allergen stimulation, Br1 decreased from 26.2 ± 18.3 to 15.5 ± 8.9% ( p = 0.031, n = 6) in the milk allergy group and increased from 15.4 ± 9.0 to 23.7 ± 11.2% ( p = 0.023, n = 8) in the milk-tolerant group. Apoptotic non-IL-10-producing regulatory B cells increased from 21.8 ± 9.3 to 38.0 ± 16.1% ( p = 0.031, n = 6) in the milk allergy group and unchanged from 28.8 ± 13.8 to 28.0 ± 15.0% ( p = 0.844, n = 8) in the milk-tolerant group. Br1 may be involved in the immune tolerance of food allergies by producing IL-10 and simultaneously undergoing apoptosis in humans. The exact roles for Br1 in immune tolerance needs to be further investigated.